ISEI - International Society of Exercise and Immunology - Abstracts of the ISEI convention in Rome 1999 (1999)
ISEI - Internationale Vereinigung für immunologische Fragen des Trainings - Zusammenfassungen der auf der Jahrestagung 1999 in Rom gehaltenen Vorträge, u.a. MUCOSAL IMMUNOEPIDEMIOLOGY OF RESPIRATORY ILLNESS IN ELITE ATHLETES (Gleeson Maree) ELITE ATHLETE IMMUNOLOGY: THE IMPORTANCE OF NUTRITION (Gleeson Michael) TRAINING STRATEGIES TO MAINTAIN IMMUNOCOMPETENCE IN ATHLETES (Pyne DB, Gleeson M, McDonald WA, Clancy RL, Perry C, Fricker PA) COMMENTS ON CLINICAL APPLICATIONS IN ATHLETES (Mackinnon LT) CD94 EXPRESSION ON NK LYMPHOCYTES - THE INFLUENCE OF EXERCISE (Horn PL, Elliott K, Pyne D, Gore C) INCREASED IMMUNO-ENDOCRINE RESPONSE TO A SECOND BOUT OF INTENSIVE ENDURANCE EXERCISE ON THE SAME DAY (Ronsen O, Rasmussen T, Pedersen BK, Bahr R) THE IMMEDIATE LEUKOCYTOSIS TO ANAEROBIC EXERCISE: EVIDENCE OF TWO SUBSEQUENT PHASES (Rätz M, Gabriel HHW, Kindermann W) APPARENT ENHANCEMENT OF EXERCISE-INDUCED ACUTEPHASE PROTEIN RESPONSE FOLLOWING VITAMIN C SUPPLEMENTATION IN ATHLETES PARTICIPATING IN AN 88 KM ULTRAMARATHON (Peters EM, Anderson R) EFFECT OF DIETARY LIPIDS AND EXERCISE ON CELLULAR IMMUNE RESPONSES AND PLASMA CYTOKINES AND HORMONES IN RUNNERS (Venkatraman JT, Pendergast DR) MUCOSAL IMMUNITY, ILLNESS AND PERFORMANCE IN SWIMMERS (Pyne DB, McDonald WA, Gleeson M, Flanagan A, Clancy RL, Fricker PA) IMMUNE PARAMETERS AND ACTUAL PERFORMANCE IN SOCCER PLAYERS (Baum M, Schünemann C, Liesen H) PRECISION OF URTI DIAGNOSIS IN TOP ATHLETES BY USING CELLULAR IMMUNE PARAMETERS (Lichtenstern C, Gabriel HHW, Kindermann W) IMMUNE FUNCTION IN FEMALE ELITE ROWERS AND NONATHLETES (Nieman DC, Nehlsen-Cannarella SL, Fagoaga OR, Henson DA, Hjertman JME) INCIDENCE OF RESPIRATORY AND GUT INFECTIONS IN ELITE SWIMMERS (Fricker PA, Gleeson M, McDonald WA, Pyne DB, Flanagan A, Clancy RL) EFFECTS OF ACUTE AND CHRONIC EXERCISE ON IMMUNE CHANGES (Sedlackova K, Ferencik M, Tibenska E, Kovacs L) EFFECT OF N-3 PUFA SUPPLEMENTATION ON THE CYTOKINE RESPONSE TO STRENUOUS EXERCISE (Toft AD, Ostrowski K, Asp S, Møller K, Vind S, Hermann C, Søndergaard SR, Pedersen BK) THE EFFECTS OF CARBOHYDRATE SUPPLEMENTATION ON NEUTROPHIL DEGRANULATION RESPONSES TO A SOCCERSPECIFIC EXERCISE PROTOCOL (Bishop NC, Blannin AK, Robson PJ, Walsh NP Gleeson M) EFFECT OF CARBOHYDRATE BEVERAGE INGESTION ON CYTOKINE AND PHAGOCYTIC RESPONSES TO TWO HOURS OF ROWING IN ELITE FEMALE ATHLETES (Bolton MR, Henson DA, Nieman DC, Nehlsen-Cannarella SL, Fagouga OR, Shannon M, Davis JM, Gaffney CT, Kelln WJ, Austin MD, Hjertman JME, Schilling BK) NK AND T CELL RESPONSE TO 2H ROWING IN ELITE FEMALE ROWERS (Hjertman JME, Nieman DC, Nehlsen-Cannarella SL, Fagoaga OR, Henson DA) BRANCHED CHAIN AMINO ACIDS SUPPLEMENTATION AND THE IMMUNE RESPONSE OF BRAZILIAN TRIATHLETES (Bassit RA, Sawada L, Bacurau RF, Martins-Jr E, Navarro F, Chamusca G, Meneguello MO, Costa Rosa LFBP) EPSTEIN-BARR VIRUS REACTIVATION IN ELITE SWIMMERS (Gleeson M, Koina C, Clancy RL, Pyne DB, Flanagan A, McDonald WA, Fricker PA) SEASONAL VARIATIONS IN TRAINING LOAD DO NOT AFFECT THE IMMUNO-ENDOCRINE RESPONSE TO ACUTE EXHAUSTIVE EXERCISE IN ELITE NORDIC SKIERS (Ronsen O, Holm K, Staff H, Opstad PK, Pedersen BK, Bahr R) SALIVARY LACTOFERRIN AS A MARKER OF MUCOSAL IMMUNOCOMPETENCE IN ELITE SWIMMERS (Cox GL, Pyne DP, Kyd JM, Gleeson M, McDonald WA, Fricker P, Cripps AW) SALIVARY IgA IN ELITE FEMALE ROWERS AND CONTROLS (Henson DA, Nieman DC, Nehlsen-Cannarella SL, Fagoaga OR, Davis JM, Bolton MR, Hjertman JM) OXIDATIVE BURST ACTIVITY OF BLOOD NEUTROPHILS IS IMPAIRED AFTER FOUR WEEKS OF OVERLOAD TRAINING IN ENDURANCE ATHLETES REVERSIBLY (Gabriel HHW, Mueller HJ, Urhausen A, Kindermann W) MODIFICATION OF HEMATOLOGICAL AND IMMUNOLOGICAL PARAMETERS IN TOP-LEVEL ATHLETES DURING ACUTE AND CHRONIC EXERCISE (Rumi C, Rutella S, Lai M, Tranquilli C, Bonini S) EFFECT OF EIGHT WEEKS OF TRAINING AND EXHAUSTIVE EXERCISE ON SOME ASPECTS OF THE IMMUNE SYSTEM (Castell L, Atchley D, Bravo N, Niemeyer, Reyes A, Bradshaw P) ALTERATIONS IN INTRACELLULAR CALCIUM SIGNALLING OF LYMPHOCYTES AFTER EXHAUSTIVE EXERCISE (Mooren FCh, Lechtermann A, Fromme A, Thorwesten L, Völker K) EFFECTS OF INCREASED WEEKLY TRAINING DURATION ON RESTING PLASMA CONCENTRATIONS OF GLUTAMINE, UREA AND IL-6 (Bagger M, Balsløv P, Pedersen BK, Pedersen PK)